The Konsep Pendidikan Islam Berbasis Cosmopolitan di Madura - Fathorrozy; Nurul Qomariyah (TADRIS: Jurnal Pendidikan Islam, 2023)
This study focuses on the concept of Islamic education in Madura based on cosmopolitanism. This study has three research focuses to be studied: the concept of Islamic education, Madurese Islam and cosmopolitanism, and cosmopolitanism-based Madurese Islamic education. By using literature research by using a descriptive approach, this study reveals that Madura is a region known known as religious and multicultural place. Madurese Islamic education is defined as learning and knowledge based on Madurese Islam. The acculturation of culture and religion merges into a unique type of Madurese Islam with a variety of Madurese traditions and Islamic values. The meaning of rationality that is shared between the concepts of Islamic Education and cosmopolitanism is humanity without foundation. Based on the theory of cosmopolitanism, the concept of Islamic education in Madura is to prioritize Islamic religious teachings that are rahmatan lil'alamin, so to create togetherness among people regardless of the background for each individuals. The concept of Madurese Islamic education based on cosmopolitanism makes a person have a high concern for humanity, regardless of his background. Cosmopolitanism is interesting to study, especially in the area of Madura.